2019
DOI: 10.1073/pnas.1900141116
|View full text |Cite
|
Sign up to set email alerts
|

Genomic plasticity associated with antimicrobial resistance in Vibrio cholerae

Abstract: The Bay of Bengal is known as the epicenter for seeding several devastating cholera outbreaks across the globe. Vibrio cholerae, the etiological agent of cholera, has extraordinary competency to acquire exogenous DNA by horizontal gene transfer (HGT) and adapt them into its genome for structuring metabolic processes, developing drug resistance, and colonizing the human intestine. Antimicrobial resistance (AMR) in V. cholerae has become a global concern. However, little is known about the identity of the resist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
103
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(106 citation statements)
references
References 21 publications
(24 reference statements)
3
103
0
Order By: Relevance
“…19 Resistant V. cholerae isolates that originated from clinical and environmental sources have been reported. 18,[20][21][22][23][24] For example, during an outbreak of cholera in Guinea-Bissau in 1996-1997, casefatality rates increased from 1% to 5.3% after the emergence of multidrug-resistant (MDR) V. cholerae. 20 Chomvarin et al reported that V. cholerae O1 strains (n = 35) isolated from clinical samples and natural surface water sources in Thailand were resistant to trimethoprim (TM)/sulfamethoxazole and/or tetracycline (TET)/or ampicillin (AMP).…”
Section: Introductionmentioning
confidence: 99%
“…19 Resistant V. cholerae isolates that originated from clinical and environmental sources have been reported. 18,[20][21][22][23][24] For example, during an outbreak of cholera in Guinea-Bissau in 1996-1997, casefatality rates increased from 1% to 5.3% after the emergence of multidrug-resistant (MDR) V. cholerae. 20 Chomvarin et al reported that V. cholerae O1 strains (n = 35) isolated from clinical samples and natural surface water sources in Thailand were resistant to trimethoprim (TM)/sulfamethoxazole and/or tetracycline (TET)/or ampicillin (AMP).…”
Section: Introductionmentioning
confidence: 99%
“…From various studies, it appears that emergence of instant antibiotic resistant clones in a susceptible bacterial population solely depends on: (i) target modifications, (ii) reduced accessibility of antibiotics to the target, (iii) decreased effective concentration of antibiotic by reducing the membrane permeability or by increasing efflux activity, and (iv) acquisition of antibiotic resistance genes from other microbial species ( Gaca et al, 2015 ; Verma et al, 2019 ; Das et al, 2020 ; Jung et al, 2020 ; Pant et al, 2020 ). A recent study has shown that the expression levels of ~300 and ~400 genes (total ~700 genes) are upregulated and downregulated, respectively, within 5 min upon induction of (p)ppGpp ( Sanchez-Vazquez, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…The most commonly used antibiotics against the bacterium includes tetracycline, erythromycin, quinolones, sulfonamides, bleomycin, chloramphenicol, and aminoglycosidase, but due to the extraordinary genomic plasticity, around 90% of the recent V. cholerae isolates have attained antimicrobial resistance against them (Verma et al, 2019). The contributing factors towards this increasing antibiotic resistance include chromosomal mutations, export of the antibiotics outside the cell through efflux pumps, and attaining genetic resistance through the exchange of plasmids, transposons, SXT elements, and autonomously replicating and integrating plasmids or integrons (Kumar et al, 2009;Kitaoka et al, 2011a;Verma et al, 2019). Integrating conjugative elements (ICE) and superintegrons from closely or distinctly related bacteriums are the major causes of antimicrobial resistance in V. cholerae (Verma et al, 2019;Das et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The contributing factors towards this increasing antibiotic resistance include chromosomal mutations, export of the antibiotics outside the cell through efflux pumps, and attaining genetic resistance through the exchange of plasmids, transposons, SXT elements, and autonomously replicating and integrating plasmids or integrons (Kumar et al, 2009;Kitaoka et al, 2011a;Verma et al, 2019). Integrating conjugative elements (ICE) and superintegrons from closely or distinctly related bacteriums are the major causes of antimicrobial resistance in V. cholerae (Verma et al, 2019;Das et al, 2020). Various strategies have been enforced to comabat these MDR strains, including the usage of various efflux pump inhibitors and quorum sensing inhibitors, but the problem remains unsolved (Hema et al, 2016;Lowrence et al, 2019).…”
Section: Introductionmentioning
confidence: 99%